Beyond Syncretism: Evidence of the Vernacularization of Islamic Theological Terms in Javanese Literature in the 19th Century - Z Zuhri (Al-Jami'ah Research Centre, 2022)
Scholars have long debated whether the relationship between Islam and Javanese culture should be considered syncretism or inculturation. This article analyzes Javanese literature to discuss post-syncretism in Islamic studies. It argues that Javanese literature exemplifies the vernacularization of Islamic theology into Javanese language and discourse. It describes how Islamic theology was used in eight Javanese texts at different historical points in the 19th Century. The leading Islamic theological terms (God, angels, Al-Qur’an, Prophet, and the Last Day) have consistent meanings in the Javanese text. Differences were only found in spelling, pronunciation, and written script that converted Arabic to Javanese and Pegon. Vernacularization functions as a tool for transmitting knowledge while the substance, meaning, and content remain unchanged. Therefore, there is no evidence of syncretism in using these terms. Syncretism may have operated in Javanese culture (e.g., Javanese Islamic rituals), but it does not appear that syncretism has penetrated the realm of theology. Accordingly, future studies on local Islam should explore discursive traditions and how knowledge has been generated alongside the process of Islamization.[Para sarjana telah berdebat lama apakah hubungan Islam dan budaya Jawa, sebaiknya berupa sinkretisme atau inkulturasi. Artikel ini membahas literatur Jawa untuk mendiskusikan post-sinkretisme dalam kajian Islam. Hasilnya menunjukkan bahwa literatur Jawa mencerminkan penyebaran teologi Islam melalui bahasa Jawa dan wacananya. Artikel ini menunjukkan teologi Islam dalam enam teks Jawa dengan penekanan historis yang berbeda pada abad 19. Istilah teologi penting seperti, Allah, malaikat, al-Qur’an, nabi dan kiamat, mempunyai makna yang tetap dalam teks Jawa. Perbedaan yang muncul hanya ejaan, pengucapan dan penulisan saat dialihkan dari bahasa Arab ke bahasa Jawa dan aksara pegon. Pribumisasi berfungsi sebagai alat transmisi pengetahuan, sedangkan substansi, makna dan kandungannya tidak berubah. Oleh karena itu tidak ada sinkretisme yang digunakan dalam pribumisasi ini. Sinkretisme mungkin berlangsung di wilayah budaya, tetapi tidak dalam konteks teologi. Dengan demikian, kajian ke depan tentang Islam lokal mengarah pada diskursif tradisi dan bagaimana pengetahuan berkembang seiring dengan proses islamisasi.]